PERSEPSI MASYARAKAT TERHADAP EKSISTENSI PESANTREN - Ruslan; Maftuhah Imam (Kariman: Jurnal Pendidikan Keislaman, 2022)
This study was motivated by the emergence of the phenomenon of the transformation of Islamic education in which many Islamic boarding schools innovate in developing an Islamic education system in the midst of society. In addition to trying to provide 'added value, the world of Islamic boarding schools is also exposed to radical issues to sexual harassment that befell their students. So this was then allegedly by some parties having raised public doubts about the existence of the pesantren itself. This study aims to describe 2 (two) things, namely: a) how the Jaddung community's perception of the existence of pesantren; b) what is the role of the Jaddung community in the sustainability of children's education in Islamic boarding schools. This study uses a qualitative research approach with the type of field research. Data collection techniques consist of observation and interviews. The data analysis technique uses interactive data analysis consisting of data condensation, data display, and drawing conclusions/verification. The results showed that the Jaddung community's perception of the existence of pesantren, among others, namely pesantren is a place of focused learning, pesantren is a bulwark of the younger generation from negative associations outside the pesantren, pesantren is a place for fostering the morals of students, pesantren is a place for fostering the independence of students, and Pesantren is a place to educate and shape the social attitudes of the students. Meanwhile, the role of the Jaddung community in the sustainability of children's education in Islamic boarding schools is as a facilitator, motivator, and mentor.